Deniably real. - Goh, Daryl Tian Sheng. (2013)
The advancement of immersive technologies results in the human obsession to represent reality through simulation experiences. These traits can be found in cinemas, gaming screens, theme parks and even virtual reality goggles. This project deals with our never-ending quest to imitate the operation of real-world processes or systems in the postmodern through the metaphor of a window. I am interested in opening a discussion on how semiotics is heavily used in the contemporaneity. It also initiates a discourse of representations and reality.